The Representation of Liberal Feminism in Cinema: A Study on Wonder Woman Film - Alda Febrianti Zulri; Azzahrah Putri Amanda; Bela Muharamah; Fauzia Dwi Marwan,; Sri Kayla Fatiha; M. Afifulloh (Journal of Literature Language and Academic Studies, 2023)
Gender equality is the goal of the feminist movement as a social movement. To understand one's position within the social framework of society, gender becomes an important analytical tool. The purpose of this study is to investigate how the discourse of feminism is portrayed in this American film by using a qualitative approach and liberal feminism as the perspective. Film Wonder Women is selected to be the primary data, and the secondary data is from another relevant text or media. Diana, who actualizes female dominance in the visual and aural aspects of the film's appearance, becomes a symbol of the feminist movement in the film. The results show that feminism is expressed in aspects through the setting place, dialog, characters and clothing.